Salivary mental stress biomarkers in COVID-19 patients - Deneva, Tanya; Ianakiev, Youri; Boykinova, Oliana (Frontiers in Medicine, 2022)
Background: During the COVID-19 pandemic the mental health disorders and level of stress show a major increase compared before the pandemic. Coronavirus-related stress is recently leading cause of negative impact on global mental health. Thus, maintaining positive mental health is as important as maintaining physical health during COVID-19. The aim of this study was to analyse salivary mental stress biomarkers as a cortisol, alpha-amylase, and chromogranin A in hospitalized patients with COVID-19 to compare their potential relationship with stress symptoms. Material and methods: A total of 80 adults hospitalized patients with moderate COVID-19 disease and control group (n=80) randomly selected were conducted as participants. Saliva cortisol (sCort), saliva alpha-amylase (sAA) saliva and chromogranin A (sCgA) were determined by ELISA method (Bio Vendor, USA). Symptoms of stress were measured with a Stress symptom checklist (SSCL). Results: The patient’s group presented significantly higher levels of sCort, sAA and sCgA com-pared with the control group. The correlation analysis showed a positive correlation with strong strength between sCort and sAA (r = 0.934, p < 0.01), as well as sAA with sCgA (r= 0.714, p < 0.01). A moderate positive correlation was found between sCort with sCgA (r = 0.618, p<0.05). Based on their stress scores from SSCL the patients were associated with high stress level (30.00%) and very high stress levels (67.5 %). In terms of the controls all the participants showed a low to moderate stress level. We found significant positive correlation between levels of stress and salivary biomarkers. Conclusion: Data from our study demonstrated that salivary biomarkers are promising tools of exploring COVID-19 related stress.